Educational attainment and problems in Indian Tribal Populations, with a focus on Tribal Women: A Theoretical Assessment (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Disparities in educational attainment exist within Indian tribal populations, especially among tribal women, despite the fact that it is a fundamental aspect of development. With an emphasis on tribal women, this theoretical evaluation probes the complex relationship between educational attainment and the various difficulties encountered by Indian tribal tribes. In this research, we review the literature and examine the various factors, such as socioeconomic status, cultural norms, insufficient infrastructure, and institutional discrimination, that prevent these communities from advancing in their education. In addition, it delves into the intricate gender dynamics inside tribal communities, illuminating the ways in which women's access to education is shaped by traditional roles and power relationships. With a focus on improving educational outcomes for tribal women and creating more inclusive development pathways, this assessment aims to shed light on these issues in order to inform policy interventions and educational initiatives that are specifically designed to meet the needs of Indian tribal communities.